РАЗРАБОТКА ИННОВАЦИОННОЙ СТРАТЕГИИ КОМПАНИИ. (Journal of Economic Research & Business Administration, 2016)
The strategy is designed to link the priorities for future development of the company to its potential level of innovation, to make a new quality control of production and the main instrument for achieving the goals of the company.